Comparative study of acid mine drainage using different neutralization methods - Zhong-sheng Huang (IWA Publishing, 2021)
Two-stage acid mine drainage (AMD) neutralization residue yield is 2.57 t/t acid equivalent using limestone and lime, 15.74% less than the 3.05 t/t acid equivalent yield from single-stage lime neutralization residue. XRD results shows that the main residue component generated by two-stage neutralization is CaSO4•0.5H2O, with a molecular weight 15.70% lower than the CaSO4•2H2O generated in single-stage neutralization. The differing amount of gypsum crystallization water from the different neutralization processes is the main cause of the different residue yields. While the actual removal rate and pH of Fe3+ are consistent with the theory, those for Zn2+, Cu2+ and Al3+ are inconsistent with the theoretical values, the error rate increasing with increasing pH. Co-precipitation with and adsorption by Fe(OH)3, mainly generated during neutralization, are the main reasons for the difference. The cost of two-stage neutralization is 16.60% less than that of single-stage neutralization when the initial reaction pH is 3.4, but the unit cost begins to increase if the initial reaction pH is raised above 3.4. When the initial pH is 4.0, the cost of two-stage neutralization exceeds that of single-stage neutralization by 4.07%. Highlights Two-stage neutralization residue yield is 15.74% less than single-stage.; Different crystallization water amount in gypsum caused different neutralization residue yield.; The co-precipitation adsorption of Fe(OH)3 is the main reason that causes the Zn2+, Cu2+ and Al3+ actual removal rates to be higher than theoretical.; The cost of the two-stage neutralization is at a minimum when the initial pH is 3.4.;